The relation between ischemia modified albumin levels and carotid intima media thickness in patients with rheumatoid arthritis. (30th March 2016) - Uslu, Ali U.; Kucuk, Adem; Balta, Sevket; Ozturk, Cengiz; Arslan, Sevket; Tekin, Levent; Kucuksen, Sami; Toker, Aysun; Kayrak, Mehmet
Abstract: Background: Cardiovascular diseases, among which atherosclerotic heart disease, are known to be one of the most important mortality and morbidity causes in patients with rheumatoid arthritis (RA). Ischemia modified albumin (IMA) is a potential marker that can be used to assess atherosclerosis‐related myocardial ischemia. Another frequently used marker for the assessment of atherosclerotic lesions is the carotid intima media thickness (CIMT). Aim: To evaluate the role that IMA has on atherosclerosis development and its clinical usability in patients with RA, by assessing the values of IMA and CIMT. Methods and materials: Our prospective study was conducted between June 2012 and March 2013 at the Rheumatology Department of Necmettin Erbakan Meram Medical School, Turkey. Fifty‐two RA patients, diagnosed according to the 1987 criteria of the American College of Rheumatology, and an age‐ and sex‐matched control group of 46 healthy subjects were included in this study. Results: No significant difference was detected between the groups with respect to age, sex and body mass index. In the patient group the IMA and CIMT values were found to be 0.37 ± 0.12 absorbance units (ABSU) and 0.80 ± 0.22 mm, respectively, while in the control group they were 0.31 ± 0.11 ABSU and 0.51 ± 0.18 mm, respectively. The IMA and CIMT values were significantly higher in the patient group ( P  =   0.022 and P  <   0.0001, respectively). A positive correlation was found between IMA, CIMT and Disease Activity Score of 28 joints ( P  =   0.016 and P  =   0.002, respectively). Conclusion: Since the values of IMA were higher in the patient group compared to controls and because of its correlation with CIMT, we suggest the use of IMA as an early marker of atherosclerosis in RA patients.